Cost-utility and budget impact analysis of adding-on apremilast to biologic therapy in the treatment of moderate to severe plaque psoriasis, an Iranian payer perspective - Marzieh Zargaran; Fatemeh Soleymani; Saman Ahmad Nasrollahi; Meysam Seyedifar; Mohammad Mehdi Ashrafian Rahaghi (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Plaque psoriasis is a chronic inflammatory disease with skin manifestations that affect the patients' quality of life negatively. The prevalence of psoriasis is approximately 2-3% worldwide and appears to be still on the increase. Due to the stigma problems, psoriasis has a significant effect on one's life that is often overlooked. The current study aimed to conduct the cost-utility evaluation and budget impact analysis of adding-on apremilast ahead of biologic therapy in the treatment of moderate to severe plaque psoriasis. The psoriatic patients who did not undergo the conventional systemic therapy were eligible to enter the defined sequences. Experimental approach: An excel-based Markov model with 40 cycles of 3 months, each of which was adopted to compare the outcomes of each exclusively administered sequence in the treatment of moderate to severe plaque psoriasis. Two exclusive therapeutic sequences were considered. In the first sequence, apremilast was followed by biologics and in the second one, biologics were administered initially without apremilast. The results were extrapolated up to 10 years. The designed Markov model was also used in budget impact analysis. The cost-saving potential of the new treatment was accounted for the next 5 years. Findings/Results: Incremental cost and incremental effect were reported in the base case scenario. Using the sequence consisting apremilast provided an additional 0.10 quality-adjusted life years and decreased total costs by about 11,100 USD per patient. These results were in line with the findings from sensitivity analysis. The cost-saving over 5 years is estimated to be around 30 million dollars for the Iran market following the use of the new treatment. Conclusion and implications: In the treatment of moderate to severe plaque psoriasis, apremilast supplementation prior to biological treatments is more cost-effective than biological treatment alone.